THE INFLUENCE OF GOOD CORPORATE GOVERNANCE, CORPORATE SOCIAL RESPONSIBILITY, AND COMPANY SIZE ON COMPANY PERFORMANCE - Yusiningtyas, Wahyu; Budiarti, Laeli (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2024)
This study analyzes the influence of Good Corporate Governance (GCG), Corporate Social Responsibility (CSR), and Company Size on company performance. A quantitative method utilized annual report data from companies listed on the Corporate Governance Perception Index (CGPI) from 2016 to 2019. The population comprised 44 companies listed on the CGPI and the Indonesia Stock Exchange, with a sample of 15 companies selected using purposive sampling. The study covered four years (2016-2019), resulting in 60 company data sets being processed and analyzed. Company performance was measured using Tobin's Q value, while GCG was assessed based on scores from the CGPI. CSR disclosure followed the Global Reporting Initiative's (GRI) requirements, with 78 items listed in GRI G4, and company size was proxied by total assets. Multiple linear regression was used for data analysis. The results indicated that GCG, CSR, and company size significantly influence company performance. Larger companies that adhere to governance practices and fulfill social responsibilities are more likely to produce proper annual reports, enhancing public trust. In the long term, such trust from investors and stakeholders can enhance company performance.